2008
DOI: 10.1158/aacr.edb-ccr-07-0617
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Poly(ADP-Ribose) Polymerase: A Two-Armed Strategy for Cancer Therapy

Abstract: Th e DNA repair pathways are protective of the host genome in normal cells; however, in cancer cells, these pathways may be disrupted and predispose to tumorigenesis or their activity may overcome the potentially cytotoxic damage caused by anticancer agents and be a mechanism of resistance. Poly(ADP-ribose) polymerase inhibitors, which block base excision repair of single-strand breaks, have entered the clinic in the last few years. Th is article discusses the interactions between the pathways of single-and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…The six genes correspond to 4.1% of significantly altered genes, with a known function, in group DON5. The protein is involved in DNA repair and has a critical role in signalling DNA single-strand breaks (Plummer and Calvert, 2007). Shifrin and Anderson (1999) showed that the addition of DON to the Jurkat human lymphoid cell line led to the activation of pro-caspase-3, leading to a higher cleavage of PARP1, a substrate of caspase-3.…”
Section: Dna Repairmentioning
confidence: 99%
“…The six genes correspond to 4.1% of significantly altered genes, with a known function, in group DON5. The protein is involved in DNA repair and has a critical role in signalling DNA single-strand breaks (Plummer and Calvert, 2007). Shifrin and Anderson (1999) showed that the addition of DON to the Jurkat human lymphoid cell line led to the activation of pro-caspase-3, leading to a higher cleavage of PARP1, a substrate of caspase-3.…”
Section: Dna Repairmentioning
confidence: 99%
“…The branching ADP-ribose polymers provide a scaffold for the assembly of repair proteins and the initiation of the complex repair reaction (Haince et al, 2005). Chemo-and radiosensitization by PARP inhibition has been the subject of many reviews (Haince et al, 2005;Plummer, 2006;Plummer and Calvert, 2007;Ratnam and Low, 2007;Lord and Ashworth, 2008). A review of the original research reports indicates that although chemo-and radiotherapy can synergize with PARP inhibitors (PARPi), the assessment of the resulting cellular responses may be limited if clonogenic survival or growth inhibition are chosen as end points (Calabrese et al, 2003(Calabrese et al, , 2004Curtin et al, 2004).…”
Section: Arrest/senescencementioning
confidence: 99%
“…PARP inhibitors block the repair of DNA single-strand breaks (SSB); unrepaired SSBs lead to the formation of DNA double-strand breaks (DSB). If DSBs cannot be repaired because of homologous recombination dysfunction, genomic instability or cell death can result (6). Therefore, PARP inhibitors may be effective against various human cancer cells with defective DNA repair genes.…”
Section: Introductionmentioning
confidence: 99%